A prospective observational study evaluating the efficacy of prophylactic internal iliac artery balloon catheterization in the management of placenta previa–accreta: A STROBE compliant article. Issue 45 (November 2017) - Fan, Yao; Gong, Xun; Wang, Nan; Mu, Ketao; Feng, Ling; Qiao, Fuyuan; Chen, Suhua; Zeng, Wanjiang; Liu, Haiyi; Wu, Yuanyuan; Zhou, Qiong; Tian, Yuan; et al.
Abstract : Abstract: We studied the efficacy of prophylactic internal iliac artery balloon catheterization for managing severe hemorrhage caused by pernicious placenta previa. This prospective observational study was conducted in Tongji Hospital, Wuhan, China. One hundred sixty-three women past 32-week's gestation with placenta previa–accreta were recruited and managed. Women in the balloon group accepted prophylactic internal iliac artery balloon catheterization before scheduled caesarean delivery and controls had a conventional caesarean delivery. Intraoperative hemorrhage, transfusion volume, radiation dose, exposure time, complications, and neonatal outcomes were discussed. Significant differences were detected in estimated blood loss (1236.0 mL vs 1694.0 mL, P  = .01), calculated blood loss (CBL) (813.8 mL vs 1395.0 mL, P  < .001), CBL of placenta located anteriorly (650.5 mL vs 1196.0 mL, P  = .03), and anterioposteriorly (928.3 mL vs 1680.0 mL, P  = .02). Prophylactic balloon catheterization could reduce intraoperative red blood cell transfusion (728.0 mL vs 1205.0 mL, P  = .01) and lessen usage of perioperative hemostatic methods. The incidence of hysterectomy was lower in balloon group. Mean radiation dose was 29.2 mGy and mean exposure time was 92.2 seconds. Neonatal outcomes and follow-up data did not have significant difference. Prophylactic internal iliac artery balloon catheterization is an effective method for managing severe hemorrhage caused by placenta previa–accreta as it reduced intraoperative blood loss, lessened perioperative hemostatic measures and intraoperative red cell transfusions, and reduce hysterectomies.